Cuidado del medio ambiente - Casa Toaquiza, Ana Isabel (2017)
The present research is about: “Environmental Care”; which objective is to diagnose the existing practices about the Environmental Care, through investigative methodologies, to propose solutions to the environmental problems in the educative institutions; for which is required a continuous, permanent and organized process with strategies that motivates the educative community; this will serve in the training of habits about the environmental care in the educative Community “Ana Pàez” developing positives and important attitudes for the environment we inhabit. For this means, graphic and field information was compiled. For the information processing was taking in account the authority, teachers and students criteria in the Educative Unit, which allowed to understand the environmental problems there were, what are the causes for this and the effects they are producing in the kids and the rest of the population. On this project was used a descriptive statistic, the same that was used for statistic tables, calculating frequencies and percentages. The obtained results helped discovered repudiation in the environmental and conservation care. Due to the current situation the present investigative project is formative and qualitative, which will be a great impact in the training habits of the kids….